Social constructivism in international relations theory - DERMAN, GİRAY SAYNUR (My University, 2021)
The main emphasis of social constructivism is the place of human consciousness or awareness in world politics. By rejecting the rationalist theory of neorealism and neoliberalism, emphasizing a sociological perspective in world politics, emphasizing normative and even material structures, constructivism emphasizes the role of identity in the formation of interests and actions and the mutual occurrence of factors and structures. Constructivism started with Thomas Hobbes (1588-1679), one of the leading thinkers of Realism. Val Dusek argues that Thomas Hobbes and Giambattista Vico, who argue that our knowledge is constructed, are the pioneers of Constructivism. Both thinkers claim that what we know best is what we do or build. Hobbes says that mathematics and its political situation are built by arbitrary decisions. Social Constructivism, especially after the 1980s, has become a common approach in dealing with and examining different issues in the field of humanities and social sciences. This study focuses on the definition of the social constructivism approach within the scope of International Relations (IR) theories and the discussions on this approach. The perspective of social construction is constructivism on change, interests, identity, cooperation, and international norms are evaluated in terms of the discipline of IR. The contribution of constructionism to international organizations and regionalization studies is important. In this context, the article focuses on the effects of social constructionism in the world in the discipline of IR and the research carried out using this approach. This study aims to show the unique aspects of constructivism and its place in IR theories, starting from the common points of the related approaches. In this context, the article first discusses the theoretical development of the discipline and constructivist approaches. Afterward, the article explains social constructivism, which is necessary for a clearer understanding of constructivist IR approaches, within the framework of the basic assumptions that distinguish constructivist approaches from the mainstream of the discipline.
Keywords: Sosyal ve Beşeri Bilimler; Siyaset Bilimi; Uluslararası İlişkiler; Social Sciences and Humanities; Political Science; International Relations; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; ULUSLARARASI İLİŞKİLER; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; INTERNATIONAL RELATIONS; POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; Social Sciences & Humanities; Social Constructivism; International Relations Theories; Hobbes; Wendt; Giddens